2022
DOI: 10.1186/s12873-022-00576-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the severity of road traffic injuries from emergency department based surveillance system in two Mexican cities

Abstract: Background Limited data from low- and middle-income countries (LMICs) on the severity of road traffic injuries (RTIs) and their relation to different variables of interest are routinely obtained. Knowledge on this subject relies on evidence from high-income countries, which might not be the same as in LMICs. This information is greatly needed to advance and inform local and regional efforts towards the United Nations’ Decade of Action and the Sustainable Development Goals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
2
Order By: Relevance
“…in which alcohol was also associated with serious injuries in road accident victims. 37 , 38 Similarly, Lasota et al . found that pedestrians under the influence of alcohol are involved in the most serious crashes resulting in death.…”
Section: Discussionmentioning
confidence: 90%
“…in which alcohol was also associated with serious injuries in road accident victims. 37 , 38 Similarly, Lasota et al . found that pedestrians under the influence of alcohol are involved in the most serious crashes resulting in death.…”
Section: Discussionmentioning
confidence: 90%
“…Because of the convenience and affordability of National Health Insurance, which covers almost 99% of the population in Taiwan, most patients with RTI visit the ED for medical attention [ 68 ]. The individuals with light injuries may be interviewed by the police before arriving at the ED, whereas those with more severe injuries are rapidly transported to the hospital in public ambulances, thus shortening the time to hospital [ 69 ]. RTIs in rural areas tend to have higher injury severity [ 12 ] and longer time to hospital [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los estudios en incidencia y prevalencia de DOV son complejos y costosos (5)(6)(7)(8)(9)(10)(11)(12). Tomando en cuenta que la falta de precisión y monitoreo sistemático de la carga de la morbilidad y la DOV en las poblaciones son centro del debate para evidenciar la magnitud del problema, la priorización de políticas y recursos son fundamentales para diseñar y ejecutar planes coherentes para desarrollar sistemas de vigilancia estadística que revelen los factores involucrados, patrones, tendencias e implicaciones (28).…”
Section: ⏐75unclassified
“…La rehabilitación de las personas con DOV es muy relevante, pero visibilizar el problema, priorizar políticas, formular planes, control en vías, comercializar vehículos más seguros y mejorar la atención a las víctimas, entre otras de reconocido impacto, es inaplazable. Aunque el riesgo e incidentes viales y sus desenlaces son prevenibles, se asume que la DOV es un fenómeno difícil de medir y monitorear, especialmente sin robustos sistemas de vigilancia epidemiológica (9)(10).…”
unclassified